(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the profound influence of social media on the evolution and expansion of modern English vocabulary in the 21st century. With the rapid growth of digital communication platforms such as Facebook, Instagram, Twitter (X), TikTok, and YouTube, language has become more dynamic, flexible, and user-driven than ever before. The study highlights how social media contributes to the creation, dissemination, and standardization of new lexical items, slang, abbreviations, and hybrid forms that reflect the cultural and technological shifts of modern society. The research investigates various linguistic phenomena, including neologisms born from online trends (e.g., “unfriend,” “hashtag,” “influencer,” “DM,” “viral”), semantic shifts of existing words (e.g., “follow,” “post,” “like”), and the increasing influence of multimodal communication (emojis, memes, GIFs) on meaning-making in digital discourse. Social media has blurred the boundaries between formal and informal language use, leading to new patterns of lexical borrowing, morphological creativity, and code-switching, particularly among younger generations. Furthermore, the article examines the sociolinguistic and pragmatic implications of this lexical innovation — how online vocabulary reflects identity, group membership, and social positioning in virtual communities. It also considers the globalizing effect of English on other languages through online communication, making English not only a lingua franca of the internet but also a living system constantly renewed through user interaction. Based on corpus-based analysis, surveys, and discourse observation, the study concludes that social media platforms function as both a laboratory and a marketplace for linguistic innovation. The new lexical items born in this environment often transcend virtual borders, entering mainstream dictionaries and everyday speech. Consequently, social media not only mirrors contemporary communication habits but actively shapes the trajectory of English vocabulary development in the digital age.